Թորոս Տարոնացու մանրանկարների պատկերագրության մարիամաբանական հենքը - Բեգլարյան, Սիրանուշ (Մատենադարան)
This study is a first attempt of analyzing the miniatures of T‘oros Taronats‘i from Mariological point of view. It examines particularly the Madonna and Child title page images of the Gospel and the image of the Wedding at Cana in Ms M6289. These miniatures are regarded as a pictorial system that offers certain exegetical reading. The iconography, the placement of the miniatures and their theological references are taken into account, and other manuscripts with similar illustrations by Taronats‘i are considered in the article. The miniatures are studied within the context of both general and Armenian Mariological exegetical writings. In this regard, the general theological definition of the image of Mary and its exegetical reading within Armenian exegetical texts are analyzed. For this purpose, the odes and hymns dedicated to Mary by Grigor Narekat‘si and John of Damascus are examined. The iconography of the miniatures is also studied within the context of historical developments and doctrinal trends of the time: the movement of the fratres unitores (who were trying to unite the catholic and Armenian churches) and the anti-unitorian political orientation of the Gladzor University are taken into account. В статье впервые исследуются миниатюры главного художника Гладзорской школы Тороса Таронаци с точки зрения мариологии. В частности в этом аспекте рассматриваются образы Богоматери с младенцем на титульном листе рукописи Матенадарана М6289 и миниатюры Брак в Кане в той же рукописи. Эти миниатюры в рукописи, иллюстрированной Таронаци, рассматриваются как изобразительная система, подлежащая экзегетическому прочтению. Учитывается иконография и размещение миниатюр и их богословский подтекст. В статье рассматриваются и другие рукописи, иллюстрированные Таронаци. Миниатюры изучены в общем мариологическом контексте и в аспекте армянских мариологических толкований. В этой связи рассматриваются гимны и оды, посвященные Марии, составленные Григором Нарекаци и Иоанном Дамаскиным. Миниатюры рассматриваются также в контексте исторических событий и доктринальных течений того времени, в частности, в связи с проблемой объединения католической и армянской церквей (XIV век) и политической позицией Гладзорского университета, противящегося унии.
Keywords: Արվեստ; Մանրանկարչություն